Antioxidant Potential and Xanthine Oxidase Inhibitory Activity of Croton sparsiflorus - AHMAD, NAEEM; SHAHWAR, DURRE; AKMAL KHAN*, MUHAMMAD; SHARIF MUGHAL†, MUHAMMAD (Asian Journal of Chemistry, 2009)
Croton sparsiflorus (traditional treatment for cuts, ulcer, fever, inflammation, hypertension, analgesic and as antivenom) extracts were examined for xanthine oxidase inhibitory (XOI) potential, antioxidant activity (DPPH• and phosphomolybdenum assays) and total phenolics. Dichloromethane (CSD), chloroform (CSC), ethyl acetate (CSEA), acetone (CSA), ethanol (CSE) and n-butanol (CSB) extracts inhibited xanthine oxidase > 50 % at 100 μg/mL concentration with IC50 values of 23.82, 17.34, 9.31, 11.35, 43.25 and 87.50 μg/mL, respectively. CSEA, CSM (methanolic extracts) and CSE extract exhibited significant DPPH• free radical scavenging potential. Total phenolics; estimated as gallic acid equivalents (mg/g of the extract); ranged from 28 to 483 (CSC, CSEA and CSA > 400 mg/g). A weak correlation of total phenolics with XOI and phosphomolybdenum assays (R2 = 0.5413 and 0.4975, respectively) proved phenolics are not the only bioactive compounds responsible for these activities. Strong correlation between total phenolics and DPPH• free radical scavenging (R2 = 0.8485) marked phenolics as the major free radical scavengers.